Prevention of type 1 diabetes in mice by tolerogenic vaccination with a strong agonist insulin mimetope - Daniel, Carolin (The Rockefeller University Press, 2011)
Type 1 diabetes (T1D) results from the destruction of insulin-secreting pancreatic β cells by autoreactive T cells. Insulin is an essential target of the autoimmune attack. Insulin epitopes recognized by diabetogenic T cell clones bind poorly to the class II I-A(g7) molecules of nonobese diabetic (NOD) mice, which results in weak agonistic activity of the peptide MHC complex. Here, we describe a strongly agonistic insulin mimetope that effectively converts naive T cells into Foxp3(+) regulatory T cells in vivo, thereby completely preventing T1D in NOD mice. In contrast, natural insulin epitopes are ineffective. Subimmunogenic vaccination with strongly agonistic insulin mimetopes might represent a novel strategy to prevent T1D in humans at risk for the disease.